Has the treaty of Segedin been found? - Kołodziejczyk, Dariusz (Balcanica Posnaniensia. Acta et studia, 1997)
The article concerns the problem of the existence and character of the Treaty of Szeged of 1444, which preceded the Varna expedition. The author analyzes the long-standing historiographical dispute over whether the treaty was actually concluded and whether its text has survived. The aim of the study is to demonstrate that the document previously regarded as a letter from Sultan Murad II is in fact the text of an Ottoman peace treaty. The author employs a diplomatic analysis of Ottoman documents and compares the text and form of the letter of 12 June 1444 with later Turkish-Polish treaties. The article presents the history of research on the Treaty of Szeged, from the discovery of the correspondence of Cyriacus of Ancona by Franciszek Pall to the interpretations of Jan Dąbrowski and Oskar Halecki. The author indicates that the document from the Ottoman chancery contains features typical of a political treaty rather than an ordinary diplomatic letter. The results of the analysis suggest that the text of the treaty has probably survived and was misclassified by earlier scholars, which is significant for the assessment of the events leading to the Battle of Varna.